2020
DOI: 10.3390/brainsci10080564
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Biomarkers in DSM-5 Anxiety Disorders: An Updated Overview

Abstract: Anxiety disorders are prevalent and highly disabling mental disorders. In recent years, intensive efforts focused on the search for potential neuroimaging, genetic, and peripheral biomarkers in order to better understand the pathophysiology of these disorders, support their diagnosis, and characterize the treatment response. Of note, peripheral blood biomarkers, as surrogates for the central nervous system, represent a promising instrument to characterize psychiatric disorders, although their role has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 269 publications
1
16
0
Order By: Relevance
“…The CSF study has brought significant benefits in understanding the pathophysiology of brain disorders [ 116 ]. However, it should be taken into account that lumbar puncture is an invasive procedure, and the components of the cerebrospinal fluid do not accurately reflect the neurochemistry of the cells in the brain [ 117 ]. Therefore, this procedure is not performed very often for psychiatric disorders, and most of the data collected concerns affective or psychotic disorders, but not anxiety disorders [ 118 ].…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…The CSF study has brought significant benefits in understanding the pathophysiology of brain disorders [ 116 ]. However, it should be taken into account that lumbar puncture is an invasive procedure, and the components of the cerebrospinal fluid do not accurately reflect the neurochemistry of the cells in the brain [ 117 ]. Therefore, this procedure is not performed very often for psychiatric disorders, and most of the data collected concerns affective or psychotic disorders, but not anxiety disorders [ 118 ].…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…In this respect, using appropriate anxiety rating scales, such as the Hospital Anxiety and Depression Scale -Anxiety (HADS-A), Generalised Anxiety Disorder-2 or 7 scale (GAD-2 or GAD-7) (Sapra et al 2020), and anti-inflammatory treatments that have effects on both anxiety and COVID-19, discussed below will be very useful, given the role of the immune system in both conditions. Very useful will be application of anxiety peripheral blood biomarkers (Vismara et al 2020). It is notable that some patients with COVID-19 display a correlation between anxiety and inflammatory markers Parker et al 2020).…”
Section: Presentation Of Anxiety In Covid-19 Patientsmentioning
confidence: 99%
“…However, a significant difference was noted in the relationship between disease severity and the increase in NGAL and PDW values due to linear regression analysis. www.iiste.org Many previous studies stated that CRP could be used as an inflammatory marker that increased in many psychiatric disorders such as schizophrenia, bipolar disease, depressive disorder, and anxiety disorder (Cunha et al, 2008;Huang & Lin, 2007;Karataş et al, 2020;Mayda et al, 2016;Vismara et al, 2020;Wei et al, 2018). A recent study reported that CRP values increased in patients who were new diagnosis OCD and did not receive any medical treatment (Karataş et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR values were evaluated in patients with schizophrenia, bipolar disease, depressive disorder, and suicidal behavior compared with healthy controls and were associated with disease severity and mortality (Kulaksizoglu&Kulaksizoglu, 2005;Sunbul et al, 2016). NLR and PLR increased in depressive disorder (Cai et al, 2017), and NLR values were high in bipolar disorder (Demircan et al, 2016;Vismara et al, 2020). Studies comparing patients with schizophrenia with controls revealed a significant increase in NLR values (Mazza et al, 2019;Moody & Miller, 2018).…”
Section: Discussionmentioning
confidence: 99%